Analysis of Risk Factors for Subjective Work Fatigue Levels Among Nurses at RS.Otak DR.Drs. M. Hatta Bukittinggi, West Sumatra, In 2024 - Djamalus, Nursanti, (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Service nursing care that is carried out home nurse Sick for 24 hours a day , very much needed readiness physical , mental and time . This is potential cause work fatigue which has an impact decline alertness and concentration , disturbed taking decisions and occurrences error or accident Work .Purpose : This Study For analyze factors risk level fatigue Work subjective on Nurses at RS.Otak.DR.Drs.M.Hatta Bukittinggi, West Sumatra 2024 .Methods: Study quantitative with design study This cross-sectional on 100 nurses at the Brain Hospital DR. Drs . M. Hatta Bukittinggi, West Sumatra in 2024. The risk factors are the characteristics individual , factor related work and environment Work Lighting . Measurement of work fatigue with a questionnaire SSRT ( Subjective Self Rating Test ) from IFRC; burden mental work with the NASA-TLX ( National Aeronautics & Space Administration Task Load Index ) questionnaire ; for role , control and satisfaction work with the COPSOG ( Copenhagen Psychosocial Questionnaire ) III questionnaire ; measurement lighting with lux meterResults: The results showed that 79% of nurses experienced mild levels of work fatigue and moderate levels of work fatigue (21%). Risk factors that had a significant relationship with the level of work fatigue were age (p 0.013; OR 6.82), nutritional status: obese (p 0.020; OR 3.77), sleep duration (p 0.050; OR 3.14).Conclusion: Implementation of fatigue management and fatigue screening periodic expected can lower level of work fatigue .